Problem Based Learning: Peningkatan Keaktifan dan Hasil Belajar IPS pada Peserta Didik di MTs Negeri 9 Gunungkidul - Cahya Widya Purnama (Jurnal Pendidikan Madrasah, 2023)
This study aims to analyze the application of the Problem Based Learning (PBL) model in increasing student activeness and learning outcomes. This study uses action research methods carried out in two cycles including planning, implementation, observation, and reflection activities. The subjects of the study were students of grade VII-D MTs Negeri 9 Gunungkidul for the 2021/2022 academic year. The results of research in cycle I and cycle II showed an increase in activeness from cycle 1 to cycle 2 with the achievement of assessment results on student learning outcomes in cycle I obtaining an average score of 54.76 with less criteria and completeness of 42.9% increased quite significantly in cycle II obtaining an average score of 68.10 with sufficient criteria and completeness of 78.6%. The problem-based learning model can be applied to social studies learning for students in grade VII.